Density and Disasters : Economics of Urban Hazard Risk - Lall, Somik V. (Oxford University Press on behalf of the World Bank, 2013)
Today, 370 million people live in cities in earthquake prone areas and 310 million in cities with a high probability of tropical cyclones. By 2050 these numbers are likely to more than double, leading to a greater concentration of hazard risk in many of the world's cities. The authors discuss what sets hazard risk in urban areas apart, summarize estimates of valuation of hazard risk, and discuss implications for individual mitigation and public policy. The main conclusions are that urban agglomeration economies change the cost–benefit calculation of hazard mitigation; that good hazard management is first and foremost good general urban management; and that the public sector must perform better in promoting market-based risk reduction by generating and disseminating credible information on hazard risk in cities.